EXCESSO DE LEGÍTIMA DEFESA: A LINHA TÊNUE ENTRE O EXCESSO DOLOSO E A EXISTÊNCIA DE CULPA (Reflection and Critique Law Magazine, 2020)
the objective of the present study is to observe the legal consequence that can be caused by the verification of the crime of excess, as well as to analyze the great difficulty of differentiating between the malicious modality and the existence of guilt. The paper also aims at pointing out relevant aspects about the exculpatory excess figure, which, although not provided for in Brazilian legislation as a criminal type, is a widely explored case-law and doctrinally.